The Artificial Intelligence Integration in the Brazilian Legal Sector: A Systematic Review - Araújo, Gabriele S.; Santana, Ewaldo E. C.; Jacob Junior, Antonio F. L.; Lobato, Fábio M. F. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246589, 2025)
Context: The National Council of Justice (CNJ) reported 140 Artificial Intelligence (AI) projects in the Brazilian Judiciary by 2023, distributed across 62 courts, representing an increase of 26.13% over the previous year. This growth reflects a digital transformation in the legal sector, focusing on increasing productivity and reducing costs and procedural times. Problem: Despite the progress, there is still a gap in the systematic understanding of the IA implementations in the legal sector due to the lack of detailed documentation that compromises transparency and hinders the overall evaluation of the efficiency of these technologies. Proposed Solution: This study conducts a systematic review to map the current panorama of AI use in the Brazilian legal sector, identifying the types of projects implemented and their scientific and technical production characteristics. IS Theory: Based on the Diffusion of Innovations Theory, which analyzes how new technologies spread in social systems. Methodology: Following Kitchenham’s systematic review methodology and the PRISMA guidelines, studies published between 2020 and 2024 were analyzed using academic databases and judicial platforms. Summarization of Results: 90 projects were identified in higher, regional, and state courts and other bodies. The main applications involve textual classification and task automation to optimize procedural efficiency. A lack of documentation and standardization was also identified, highlighting the need for more project transparency. Contributions and Impact on IS: The study maps the intersection between AI, Information Systems, and the legal sector in Brazil, highlighting topics that need more attention. It contributes to the advancement of adaptive IS architectures and provides a theoretical-empirical basis to drive the digital transformation of the judicial system.